A case report of congenital pemphigus syphiliticus in a preterm neonate: Insights into diagnosis, treatment, and long-term follow-up in a resource-limited country (Cambodia) - Bormey Sim; Vuthny Din; Sethikar Im; Sakviseth Bin (SAGE Open Medical Case Reports)
Congenital syphilis remains a preventable cause of neonatal morbidity, often resulting from undiagnosed or untreated maternal infection. We report a case of a late-preterm infant born to a mother with late latent syphilis underdiagnosed during pregnancy. Vertical transmission occurred transplacentally, given that the neonate presented with respiratory distress and pathognomonic signs such as pemphigus on both feet at birth. Laboratory evaluation confirmed syphilis infection, with high titer of RPR (Rapid Plasma Reagin) and TPHA ( Treponema Pallidum Hemagglutination Assay) and markedly elevated inflammatory markers. The infant received a 10-day course of intravenous penicillin, leading to rapid clinical improvement and resolution of skin lesions. Serial serological monitoring showed a steady decline in RPR titers, achieving seronegativity by 6 months, accompanied by catch-up growth by 1 year. This case underscores the importance of thorough antenatal screening, early diagnosis, and treatment of maternal syphilis, and comprehensive management and follow-up of infected infants, particularly in resource-limited settings as Cambodia.